The foraging tactics of chestnut-winged Babbler (Stachyris erythroptera) and Abbott’s Babbler (Malacocincla abbotti) in a Lowland Rainforest, Malaysia - Mohammad Saiful Mansor,; Rosli Ramli,; Shahrul Anuar Mohd Sah, (Universiti Kebangsaan Malaysia, 2015)
Foraging pattern of Chestnut-winged Babbler (Stachyris erythroptera) and Abbott’s Babbler (Malacocincla abbotti) was studied in Lenggong Valley, Perak from July 2010 until July 2011. The study examines the patterns of foraging height, foraging substrates and attack manoeuvres of two babbler species (Family: Timaliidae), to explain how these trophically similar species can coexist in the same habitat; a central question in ecology. Information on the foraging height, foraging substrate and attack manoeuvres was collected independently for each foraging bird. Principal component analysis and Pearson’s correlation analysis showed that these two species used similar proportion of foraging height (>0-2 m above the ground) and foraging substrate (dead leaves), but differed in the use of attack manoeuvres. The Chestnut-winged babbler used primarily stretching manoeuvre, whereas the Abbott’s babbler used primarily gleaning manoeuvre. This niche separation allowed these species to coexist in the same area, thus follows the Gause’ Law of competitive exclusion, that states two species occupying the same niches will not coexist forever.